Correction: Syntheses, structures, optical properties and biological activities of bimetallic complexes. Issue 12 (11th February 2015) - Mahato, Mamata; Dey, Dhritiman; Pal, Souvik; Saha, Sudeshna; Ghosh, Abhrajyoti; Harms, Klaus; Nayek, Hari Pada
<x xml:space="preserve">Abstract</x> Correction for 'Syntheses, structures, optical properties and biological activities of bimetallic complexes' by Mamata Mahato et al., RSC Adv., 2014, 4, 64725–64730.